51.1k views
5 votes
What is the product?
(-3s+2t)(4s-t)

2 Answers

0 votes

Answer:

-12s²+11st-2t²

Explanation:

(-3s+2t)(4s-t)

=−3s(4s) −3s(−t)+2t(4s)+2t(−t)

=-12s²+3st+8st-2t²

=-12s²+11st-2t²

User TanuAD
by
5.4k points
1 vote

Answer:

12s² + 11st - 2t²

Explanation:

Each term in the second factor is multiplied by each term in the first factor, that is

- 3s(4s - t) + 2t(4s - t) ← distribute both parenthesis

= - 12s³ + 3st + 8st - 2t² ← collect like terms

= - 12s² + 11st - 2t²

User Diwas Poudel
by
5.2k points